A randomised controlled trial to compare the clinical and cost-effectiveness of prism glasses, visual search training and standard care in patients with hemianopia following stroke: a protocol. Issue 7 (17th July 2014) - Rowe, F J; Barton, P G; Bedson, E; Breen, R; Conroy, E J; Cwiklinski, E; Dodridge, C; Drummond, A; Garcia-Finana, M; Howard, C; Johnson, S; MacIntosh, C; et al.
Abstract : Introduction: Homonymous hemianopia is a common and disabling visual problem after stroke. Currently, prism glasses and visual scanning training are proposed to improve it. The aim of this trial is to determine the effectiveness of these interventions compared to standard care. Methods and analysis: The trial will be a multicentre three arm individually randomised controlled trial with independent assessment at 6 week, 12 week and 26 week post-randomisation. Recruitment will occur in hospital, outpatient and primary care settings in UK hospital trusts. A total of 105 patients with homonymous hemianopia and without ocular motility impairment, visual inattention or pre-existent visual field impairment will be randomised to one of three balanced groups. Randomisation lists will be stratified by site and hemianopia level (partial or complete) and created using simple block randomisation by an independent statistician. Allocations will be disclosed to patients by the treating clinician, maintaining blinding for outcome assessment. The primary outcome will be change in visual field assessment from baseline to 26 weeks. Secondary measures will include the Rivermead Mobility Index, Visual Function Questionnaire 25/10, Nottingham Extended Activities of Daily Living, Euro Qual-5D and Short Form-12 questionnaires. Analysis will be by intention to treat. Ethics and dissemination: This study has been developed and supported by the UK Stroke Research Network Clinical Studies Group working with service users. Multicentre ethical approval was obtained through the North West 6 Research ethics committee (Reference 10/H1003/119). The trial is funded by the UK Stroke Association. Trial Registration: Current Controlled Trials ISRCTN05956042 . Dissemination will consider usual scholarly options of conference presentation and journal publication in addition to patient and public dissemination with lay summaries and articles. Trial Registration: Current Controlled Trials ISRCTN05956042 .